Stimming and Stereotypy: Situating Improvisation at the Margins of Sensibility - Sokolov-Gonzalez, Jake (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2026)
This article traces the ways that improvisation is being taken up by three distinct theories of sensory integration. The first stems from my experience of living with sensory dysfunction and extends into theories of autism. The second is the computational neuroscientific theory of predictive processing, and the third is an ecological approach to action and perception. The second and third models put forward the notion of abductive reason as a description of their cognitive processes, which, raised into consciousness they call improvisation.